Pentingnya Profesionalisme Guru dalam Pendidikan - Syamsiah Nur; Mardiah Mardiah (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2020)
This study aimed to determine the importance of teacher professionalism in education. This study used descriptive qualitative research by describing the importance of professionalism for teachers. One of the most important factors in realizing the goals of education in Indonesia is the teacher's professionalism in the implementation of teaching and learning activities. The problem today is that many students are confused after completing their education. Where to go? What kind of work? What student's want with this certificate? More unemployment means education has a lack of quality. Educational institutions that were supposed to produce knowledgeable students were lost due to the unprofessional quality teachers. The results showed that professionalism is very important for teachers and is a demand in a profession so that there are laws that regulate the obligations of professional teachers, there are several assumptions that underlie the needs for teacher professionalism in education, and there are some special requirements that must be met by professionalism teachers in education.